MAKOTA (masker konektor & strap) sebagai ide bisnis guru di masa pandemi Covid-19 - Primanita Sholihah Rosmana; Sofyan Iskandar; Kanda Ruskandi; Erna Suwangsih; Asep Sujana; Luthfi Wulandari; Indah Fitria (IKIP SILIWANGI, 2022)
The COVID-19 pandemic takes negative effect to Indonesian economy. Prospective teachers and teachers who are affected need to make efforts to improve the economy. One alternative that can be done is by doing entrepreneurship. Based on Kemenkopukm data (2015) the number of entrepreneurs in Indonesia is relatively low, at 1.65% of the total population. This figure is below the ASEAN average, which is at 4%. The results of a survey on students at UPI Purwakarta Campus 80% have problems in determining the products to be sold. MAKOTA (Connector & Strap Mask) can be one of the business ideas during the covid-19 pandemic. The online MAKOTA workshop was held on Wednesday, September 29, 2021. This activity was attended by 53 participants from various regions in West Java Province using the zoom meeting platform. The offline MAKOTA workshop was held on Friday, October 1, 2021, which was attended by 20 participants from various regions in West Java Province. After this service activity, participants can make connector and strap products. The techniques learned by the participants at the MAKOTA workshop can be applied to other accessories so that they can produce various products as entrepreneurial ideas. Participants can make attractive product photos to be marketed and sell products offline and online in marketplaces and social media such as Instagram and Facebook.